A genetic variant in primary miR-378 is associated with risk and prognosis of hepatocellular carcinoma in a Chinese population. - Jiaze An; Jibin Liu; Li Liu; Yao Liu; Yun Pan; Mingde Huang; Fuzhen Qi; Juan Wen; Kaipeng Xie; Hongxia Ma; Hongbing Shen; Zhibin Hu (PLoS ONE, 2014)
BACKGROUND: MiR-378 has been reported to be related to cell survival, tumor growth and angiogenesis and may participate in hepatocellular carcinoma (HCC) development and prognosis. Genetic variants in primary miR-378 (pri-miR-378) may impact miR-378 expression and contribute to HCC risk and survival. This study aimed to assess the associations between a genetic variant in primary miR-378 and HCC susceptibility and prognosis. METHODS: We conducted a case-control study to analyze the association of rs1076064 in pri-miR-378 with hepatocellular carcinoma risk in 1300 HCC patients with positive hepatitis B virus (HBV) and 1344 HBV carriers. Then, we evaluated the correlation between the polymorphism and hepatocellular carcinoma prognosis in 331 HCC patients at either intermediate or advanced stage without surgical treatment. RESULTS: The variant genotypes of rs1076064 were associated with a decreased HCC risk in HBV carriers [Adjusted odds ratio (OR) = 0.90, 95% confidence intervals (CI) = 0.81-1.00, P = 0.047]. Moreover, HCC patients with the variant genotypes were associated with a better survival [Adjusted hazard ratio (HR) = 0.70, 95% CIs = 0.59-0.83, P<0.0001 in an additive genetic model]. The reporter gene assay showed that the variant G allele of rs1076064 exerted higher promoter activity than the A allele. CONCLUSIONS: These findings indicate that rs1076064 may be a biomarker for HCC susceptibility and prognosis through altering pri-miR-378 transcription.